Lycopene, sulforaphane, quercetin, and curcumin applied together show improved antiproliferative potential in colon cancer cells in vitro. Issue 4 (11th February 2019) - Langner, Ewa; Lemieszek, Marta Kinga; Rzeski, Wojciech
Abstract: Lycopene, sulforaphane, quercetin, and curcumin, ingredients of daily diet, show significant anticancer and chemopreventive potential; however, no data are available showing thorough evaluation of jointly used phytochemicals on cancer cell proliferation. Here, we compare anticancer potential of mentioned substances applied separately or in combination (as MIX) by measuring mitochondrial activity (MTT test), DNA synthesis (BrdU test) and lactate dehydrogenase release (LDH test) in colon epithelial (CCD841 CoTr), and colon cancer (HT‐29, LS174T) cells. Additive inhibitory effect of simultaneously used phytochemicals on cancer cells proliferation has been shown. In epithelial cells, tested combination effectively inhibited mitochondrial activity, but not DNA synthesis. LDH test revealed cytotoxicity of tested mixture against cancer cells without negative effect on normal cells. Furthermore, we demonstrated that MIX enhances antiproliferative effect of common cytostatics: 5‐fluorouracil and cisplatin. Presented data suggest chemopreventive potential of the proposed combination of natural substances and their usefulness as adjuvant strategy during chemotherapy. Practical applications: Colorectal cancer is one of the most common causes of cancer death worldwide. Since its development and progression is strongly correlated with dietary habits, healthy diet as well as supplementation with proved anticancer agents seems to be reasonable strategy of colon cancer prevention and treatment. In the present study, we have focused on four natural compounds abundantly found in daily diet i.e., lycopene, sulforaphane, quercetin, and curcumin, with well established anticancer potential. Their individual and collective impact both on normal colon epithelium cells and colon cancer cells viability, growth, and proliferation was examined. Furthermore, activity of the substances combined as MIX to influence antiproliferative potential of commonly used in colon cancer treatment cytostatics, 5‐fluorouracil, and cisplatin was verified. Proposed in the study combination of phytochemicals with experimentally proven antiproliferative activity may propose an effective strategy for prevention and treatment of colon cancer.